Impact of Decentralization on Restructuring Nepal - Ghimire, Tara Nath (Tribhuvan University Journal, 2023)
This article discusses how decentralization laws have affected the implementation of federalism in Nepal, as well as when and how it started. Federalism and decentralization are different issues but the practice of decentralization in Nepal in different periods that has affected the existing governance system. Politics and state forms have also been influenced by modern and post-modern thought. This research focuses on the impact of decentralization laws on federalism. The study uses only secondary data to examine what old decentralization practices we reemployed during state restructuring in Nepal. Since ancient times, Nepal has been ruled by a unitary system. Nepal's institutionalized decentralization history is not long. Before Nepal's unification, there were various minor states. At that time, it was necessary to increase the state size based on power. Nepal does not have a long history of legal rule though decentralization has been used throughout history. Some of the effects of the old laws are reflected in the updated laws. This study examines how decentralization affects federalism throughout different historical periods. It reveals how old decentralization laws influenced federalism. Using descriptive and analytical methods, the study came to its conclusion.